Colon, Rectum and Anus: Anatomic, Physiologic and Diagnostic Bases for Disease Management - Ratto, Carlo; Parello, Angelo; Donisi, Lorenza; Litta, Francesco (Springer International Publishing : Imprint: Springer, 2017)
.
Keywords: koloproktologie; nemoci konečníku; coloproctology; rectum diseases; elektronické knihy; sborníky; electronic books; papers of several authors